A kind of crystal preparation method of ammonium heptamolybdate
By using a compound chelating agent to adsorb molybdate and combining steps such as crushing, oxidative calcining, alkali leaching, etc., the problems of complex preparation process and low purity of ammonium heptamolybdate in low-grade molybdate are solved, and the preparation of high-purity ammonium heptamolybdate is achieved.
Patent Information
- Application Number
- CN202411957438.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
When processing low-grade molybdenum ore, the process of preparing ammonium heptamolybdate is complex and costly, resulting in low purity of the product and difficult to meet the requirements of industrial applications.
The molybdate in low-grade molybdenum ore is adsorbed by compound chelating agents, and the enrichment of molybdenum elements and the preparation of high purity of ammonium heptamolybdate is achieved through steps such as pulverization, oxidative calcination, alkali leaching, chelation, and desorption.
The preparation process of ammonium heptamolybdate was simplified and the impurity content was reduced. The purity of ammonium heptamolybdate was more than 99.028%, meeting the chemical purity requirements.
Smart Images

Figure CN119370889B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of molybdenum metallurgy, and more specifically, to a method for preparing ammonium heptamolybdate by crystallization. Background Art
[0002] Ammonium heptamolybdate is an important raw material for preparing catalysts and metallic molybdenum. Due to its good water solubility, in the field of organic synthesis, it can be used as a liquid-phase oxidation catalyst in processes such as petroleum hydrogenation, desulfurization and denitrification, and styrene monomer preparation.
[0003] The common method of obtaining ammonium heptamolybdate by treating molybdenum ore can be divided into two types according to the different processes: pyrometallurgical roasting and ammonia leaching and full hydrometallurgical process. The full hydrometallurgical process has low requirements on the grade of molybdenum ore and low content of toxic substances in reaction byproducts, but it also has the problems of complex operation process and high equipment requirements. Therefore, the current industrial production mostly uses the process of pyrometallurgical roasting and ammonia leaching to treat molybdenum ore to obtain ammonium heptamolybdate.
[0004] The pyrometallurgical roasting ammonia leaching process has certain requirements for the grade of molybdenum ore, and most of the molybdenum ore used is high-grade molybdenum ore with high molybdenum content and few impurities. However, the reserves of such high-grade molybdenum ore are small, and the mining cost is high. At present, most of the mined molybdenum ore is still low-grade molybdenite with low molybdenum content. The ammonium heptamolybdate prepared by the pyrometallurgical roasting ammonia leaching process for treating low-grade molybdenite has low purity, which is difficult to meet the requirements of industrial application for the purity of ammonium heptamolybdate.
[0005] A Chinese patent application with application publication number CN104649322A discloses a method for preparing high-purity ammonium heptamolybdate. In the application, the paste of roasted molybdenum concentrate after purification, extraction, slurry adjustment and impurity removal is directly used in the production of ammonium heptamolybdate, and the molybdenum content in the material is continuously increased through extraction, back extraction and ultrasonic-assisted purification technology, and finally high-purity ammonium heptamolybdate is obtained.
[0006] Although the above patent application document enriches molybdenum elements and produces high-purity ammonium heptamolybdate through a series of treatments, the treatment process is too complicated, and the slurry adjustment, extraction, and back extraction steps in the process also consume a lot of solvents, which increases the cost of industrial production. Therefore, there is still a need to find a simple process and low-impurity ammonium heptamolybdate preparation process. Summary of the invention
[0007] In order to further simplify the preparation process of ammonium heptamolybdate and reduce the impurity content in ammonium heptamolybdate, the present application provides a crystallization preparation method of ammonium heptamolybdate.
[0008] A method for preparing ammonium heptamolybdate by crystallization comprises the following steps:
[0009] (S01) taking low-grade molybdenite, crushing and ball-milling to obtain molybdenum ore sand;
[0010] (S02) taking molybdenum ore and oxidizing and calcining it, adjusting the temperature gradient to 5-8°C / min, raising the temperature to 600-650°C, maintaining the temperature for 2-3h, and cooling to obtain molybdenum roasted sand;
[0011] (S03) dispersing the molybdenum roasted sand with a sodium hydroxide solution, adjusting the temperature to 35-45° C., stirring and impregnating, filtering, and obtaining a leachate;
[0012] (S04) adding a composite chelating agent to the leaching solution, stirring and immersing, and then filtering and collecting the precipitate to obtain a chelate; the composite chelating agent is prepared by reacting carboxyl-modified silica particles with an amino acid source;
[0013] (S05) adding the chelate to a desorption solution for desorption treatment to obtain a sodium molybdate solution;
[0014] (S06) Take a sodium molybdate solution, add dilute sulfuric acid to adjust the pH for the first time, then add ammonia water for ammonia leaching, adjust the pH to 6.5-7.0 again, control the temperature to 55-70°C, keep the temperature constant for 3-5 hours, then cool it to 8.5-10.5°C at a temperature drop of 0.5°C / min, let it stand for 8-10 hours, take the bottom crystalline material, wash it with alcohol and then crush it to obtain ammonium heptamolybdate.
[0015] In the step (S04), the preparation steps of the composite chelating agent are as follows:
[0016] (I) adding ethyl orthosilicate dropwise to the pre-solution to react, filtering the precipitate, drying at 55-60°C, and grinding to obtain silicon dioxide powder;
[0017] (II) mixing and dispersing the silane coupling agent and the acid anhydride, reacting, adding silica powder and water, continuing the reaction, and then filtering and washing the precipitate with alcohol to obtain carboxyl-modified silica particles;
[0018] (III) Mixing an amino acid source with tert-butyl acetate, placing in an ice bath, adding an acid solution dropwise, reacting, and then adjusting the pH of the system to 6.5-7, extracting the organic phase, and rotary evaporating at 35-40° C. to obtain a solid powder;
[0019] (IV) Dispersing the solid powder, adding carboxyl-modified silica particles, aluminum chloride and anhydrous sodium sulfate, and mixing, adjusting the temperature to 65-75°C, allowing the mixture to stand after the reaction, filtering the solid portion, washing with water and filtering again, dissolving the precipitate with dichloromethane, placing it in an ice bath, adding trifluoroacetic acid as an acidolysis agent, stirring, filtering the precipitate, and drying it to obtain a composite chelating agent.
[0020] By adopting the above technical scheme, the enrichment of molybdenum in low-grade molybdenite can be achieved through crushing, calcination, alkali leaching, chelation, and desorption steps. The composite chelating agent used is obtained by grafting carboxyl-modified silica particles with amino acids through acylation reaction. The amide group and the double bond oxygen site of the carboxyl group on the amino acid can chelate with the molybdate to form a coordination compound with the molybdenum atom as the central atom and the double bond oxygen as the ligand, thereby achieving selective adsorption of the molybdate in the leachate, and after filtering, precipitating and desorption treatment, a solution of sodium molybdate with high purity can be obtained. At the same time, in the desorption process, the composite chelating agent is separated from the molybdate, and the obtained precipitate can be used as a composite chelating agent again for the selective adsorption of molybdate in the leachate after drying, thereby realizing the recycling of the composite chelating agent.
[0021] Preferably, in step (I), the pre-solution is prepared by mixing anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate in a volume ratio of (45-55): (15-20): (10-12): (1-1.5), and stirring at 30-45°C for 1-2h.
[0022] By adopting the above technical solution, the obtained pre-solution is used as a precursor solution for the hydrolysis of ethyl orthosilicate, providing a template for the growth of particles of ethyl orthosilicate added later, and finally obtaining silicon dioxide powder after pulverization.
[0023] Preferably, in step (II), the silane coupling agent is γ-aminopropyltriethoxysilane; and the acid anhydride is any one of succinic anhydride and glutaric anhydride.
[0024] By adopting the above technical scheme, γ-aminopropyl triethoxysilane is used as a silane coupling agent to react with succinic anhydride or glutaric anhydride, and the amino group on the γ-aminopropyl triethoxysilane undergoes nucleophilic substitution with the acid anhydride to obtain an amide group. During the reaction, the acid anhydride is ring-opened, and a carboxyl group can be introduced into the γ-aminopropyl triethoxysilane. At the same time, the ethoxy position of the γ-aminopropyl triethoxysilane condenses with the hydroxyl group on the surface of the silica powder to form a stable graft structure, and finally obtains carboxyl-modified silica particles.
[0025] Preferably, in step (III), the amino acid source is prepared by mixing citrulline, β-alanine and γ-aminobutyric acid in a mass ratio of (0.5-0.8): (1.2-1.5): (0.3-0.5).
[0026] By adopting the above technical scheme, the amino acid source is the molybdate chelating ligand component, and the introduction of multiple amino acid sources can enhance the chelating effect. At the same time, the introduction of the amino acid source increases the chain length of the compound chelating agent, reduces the chelating resistance between the negatively charged ion molybdate and the carboxyl-modified silica particles, and the compound chelating agent prepared with the above amino acid types and ratios has the best effect.
[0027] Preferably, in step (III), the acid solution is perchloric acid with a mass concentration of 35%-50%.
[0028] By adopting the above technical scheme, perchloric acid is a catalyst for the tert-butyl esterification reaction. The use of perchloric acid with the above mass concentration can promote the tert-butyl esterification reaction. By inserting a tert-butyl ester group on the amino acid, the large steric hindrance effect of the tert-butyl ester group can effectively shield the carboxyl group on the amino acid, thereby avoiding the destruction of the carboxyl structure in the subsequent reaction and the large generation of side reaction products.
[0029] Preferably, in step (IV), the acidolysis agent is trifluoroacetic acid.
[0030] By adopting the above technical scheme, trifluoroacetic acid as an acidolysis agent can remove the tert-butyl ester protecting group at the carboxyl position of the amino acid, thereby exposing the carboxyl active group on the amino acid.
[0031] Preferably, in the step (S05), the desorption liquid is prepared by mixing petroleum ether and citric acid in a mass ratio of (500-550):1.
[0032] By adopting the above technical solution, citric acid can further coordinate with the still unsaturated molybdenum atoms in the chelate, changing the coordination structure of the molybdenum atoms, and the weakly polar petroleum ether further reduces the stability of the coordinated bonding structure. The use of a two-component desorbent provides a favorable environment for the desorption of molybdate.
[0033] Preferably, in the step (S05), the desorption treatment is:
[0034] The chelate was mixed with the desorption liquid, stirred for 1-2 hours, then slowly heated to 55-65°C at a rate of 5°C / min, the ultrasonic frequency was controlled at 20-20.5kHz, ultrasonic treatment was performed for 0.5-1h, and filtered to obtain a solid phase and a sodium molybdate solution.
[0035] By adopting the above technical scheme, under the combined treatment of heating and ultrasound, the weak steady-state structure formed by the citric acid-amino acid-molybdenum atom complex is disintegrated, the molybdate ion is desorbed from the complex chelate, and the solid phase can be recycled as a complex chelating agent after washing and drying.
[0036] Preferably, in the step (S06), dilute sulfuric acid is added to adjust the pH to 4.2-5.5 for the first time.
[0037] By adopting the above technical solution, when the pH of the system is 4.2-5.5, the molybdenum element in the system is mainly in the form of Mo7O 24 6- The yield of ammonium heptamolybdate can be maximized by adjusting the pH of the sodium molybdate solution.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. This application uses a composite chelating agent to adsorb molybdate in low-grade molybdenite. The amide group in the composite chelating agent and the double bond oxygen site of the carboxyl group on the amino acid can chelate with the molybdate to form a chelate with the molybdenum atom as the central atom and the double bond oxygen as the ligand, thereby achieving selective adsorption of molybdate in the leachate. After filtering, precipitating and desorption treatment, a sodium molybdate solution with high purity can be obtained, which can be used for the refining of ammonium heptamolybdate.
[0040] 2. In the present application, it is preferred to use a composite chelating agent obtained by grafting carboxyl-modified silica particles with an amino acid source through an acylation reaction. During the desorption process, the composite chelating agent is separated from the molybdate, and the obtained solid phase can be dried and reused as a composite chelating agent for the selective adsorption of molybdate in the leachate, thereby realizing the recycling of the composite chelating agent.
[0041] 3. The purity of the obtained ammonium heptamolybdate can reach above 99.028% by using the composite chelating agent of the present application to treat low-grade molybdenite, meeting the chemical purity requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a process flow chart for preparing ammonium heptamolybdate in this application.
[0043] Figure 2 This is the XRD pattern of the powder obtained after the sodium molybdate solution is evaporated to dryness in Example 1 of the present application.
[0044] Figure 3 This is the XRD pattern of ammonium heptamolybdate prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0045] Example 1
[0046] The crystallization preparation method of ammonium heptamolybdate in the present embodiment is as follows:
[0047] (S01) Take 300g of low-grade molybdenite and crush it using a 125mmX150mm jaw crusher with a power of 3KW for 30 minutes. Then transfer the crushed material to a ball mill, control the ball mill speed to 135rpm, the ball-to-material ratio to 2:1, and grind for 1.5 hours to obtain molybdenum ore sand.
[0048] (S02) Put the molybdenum ore into a muffle furnace, control the temperature rise gradient to 5°C / min, rise to 600°C, then keep the temperature constant for 2 hours and then cool naturally to obtain molybdenum roasted sand.
[0049] (S03) Add molybdenum roasted sand into 5L of sodium hydroxide solution with a molar concentration of 2.5mol / L for dispersion, adjust the temperature to 35°C, stir at a speed of 100rpm, continue for 8h, and then filter to obtain a leachate.
[0050] (S04) Add 20 g of a composite chelating agent to the leachate, control the stirring speed to 100 rpm, and continue for 0.5 h, then filter and collect the precipitate to obtain a chelate.
[0051] (S05) Add the chelate to 500 mL of desorption solution, stir for 1 hour, then slowly heat to 55°C at a rate of 5°C / min, and control the ultrasonic frequency to 20kHz for 0.5 hour. Filter the liquid phase, extract with water, remove petroleum ether and impurities, and obtain a sodium molybdate solution.
[0052] (S06) Take a sodium molybdate solution, add dilute sulfuric acid with a molar concentration of 0.05 mol / L, adjust the pH of the system to 4.2, then add ammonia water, adjust the pH to 6.5 again, and at the same time increase the system temperature to 55°C, adjust the stirring speed to 150 rpm, and continue for 3 hours, then cool to 8.5°C with a cooling gradient of 0.5°C / min, let it stand for 8 hours, take the bottom crystalline material, wash with alcohol and then crush it to obtain ammonium heptamolybdate.
[0053] In this embodiment, the preparation steps of the composite chelating agent are as follows:
[0054] (I) Take 75 mL of the pre-solution and add 12 mL of ethyl orthosilicate dropwise at a rate of 0.5 mL / min. Control the magnetic stirring speed to 100 rpm. After the addition is complete, continue stirring and reacting for 3 hours. Then filter and collect the precipitate. After drying at 55°C, grind for 3 minutes to obtain silica powder.
[0055] (II) Weigh 1.1 g of γ-aminopropyltriethoxysilane and 0.5 g of succinic anhydride, disperse them evenly in 45-50 mL of tetrahydrofuran, control the magnetic stirring rate to 150 rpm, react for 0.5 h, then add 10 g of silica powder and 10 mL of deionized water, continue to react for 3 h, then filter the precipitate, wash it with alcohol twice, and you can get carboxyl-modified silica particles.
[0056] (III) 1.2 g of the amino acid source was mixed with 5 mL of tert-butyl acetate, and the mixture was stirred in an ice bath for 5 min. Then, 0.3 mL of 35% perchloric acid was added to the system, and the magnetic stirring speed was adjusted to 100 rpm. The reaction was carried out for 3 h. Then, a sodium hydroxide solution with a molar concentration of 0.05 mol / L was used to adjust the pH of the system to 6.5. Ether was used for extraction, and the upper organic phase was taken and rotary evaporated at 35 °C to obtain a solid powder.
[0057] (IV) The solid powder was dispersed with 50 mL of acetone, and then carboxyl-modified silica particles were added, and the magnetic stirring speed was controlled to 250 rpm for 3 min, and then 0.3 g of aluminum chloride and 2 g of anhydrous sodium sulfate were added to the system, and the temperature was adjusted to 65 ° C, and the magnetic stirring speed was adjusted to 50 rpm, and the reaction was performed for 5 h. Then, the mixture was allowed to stand at room temperature for 10 h, and the solid part was filtered, washed with water twice, and filtered again, and the precipitate was added to 45 mL of dichloromethane solution, and 3 mL of trifluoroacetic acid was added under ice bath conditions. After stirring for 2 h, the precipitate was filtered again and dried to obtain a composite chelating agent.
[0058] Among them, the chemical composition (%wt) of low-grade molybdenite is: SiO269.27%, Al2O37.63%, MoS28.25%, CuFeS27.93%, CaO 3.24%, Fe2O31.25%, MgO 1.04%, and others 1.39%. The desorption solution is prepared by mixing petroleum ether and citric acid in a mass ratio of 500:1. The pre-solution is prepared by mixing anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate in a volume ratio of 45:15:10:1 and stirring at 30°C for 1h. The amino acid source is prepared by mixing citrulline, β-alanine, and γ-aminobutyric acid in a mass ratio of 5:12:3.
[0059] Example 2
[0060] The crystallization preparation method of ammonium heptamolybdate in the present embodiment is as follows:
[0061] (S01) Take 300g of low-grade molybdenite and crush it using a 125mmX150mm jaw crusher with a power of 3KW for 30 minutes. Then transfer the crushed material to a ball mill, control the ball mill speed to 135rpm, the ball-to-material ratio to 2:1, and grind for 1.5 hours to obtain molybdenum ore sand.
[0062] (S02) Put the molybdenum ore into a muffle furnace, control the temperature rise gradient to 5°C / min, rise to 625°C, then keep the temperature constant for 2.5 hours and then cool naturally to obtain molybdenum roasted sand.
[0063] (S03) Add molybdenum roasted sand into 5L of sodium hydroxide solution with a molar concentration of 2.5mol / L for dispersion, adjust the temperature to 40°C, stir at a speed of 100rpm, continue for 10h, and then filter to obtain a leachate.
[0064] (S04) Add 25 g of a composite chelating agent to the leachate, control the stirring speed to 150 rpm, and continue for 0.5 h, then filter and collect the precipitate to obtain a chelate.
[0065] (S05) The chelate was added to 600 mL of desorption solution, stirred for 1 h, and then slowly heated to 60 °C at a rate of 5 °C / min, while ultrasonically controlling the ultrasonic frequency to 20.5 kHz for 1 h. The liquid phase was filtered and extracted with water to remove petroleum ether and impurities to obtain a sodium molybdate solution.
[0066] (S06) Take a sodium molybdate solution, add dilute sulfuric acid with a molar concentration of 0.05 mol / L, adjust the pH of the system to 4.5, then add ammonia water, adjust the pH to 7.0 again, and at the same time increase the system temperature to 65°C, adjust the stirring speed to 175 rpm, and continue for 5 hours, then cool to 9°C with a cooling gradient of 0.5°C / min, let it stand for 10 hours, take the bottom crystalline material, wash with alcohol and then crush it to obtain ammonium heptamolybdate.
[0067] In this embodiment, the preparation steps of the composite chelating agent are as follows:
[0068] (I) Take 75 mL of the pre-solution and add 15 mL of ethyl orthosilicate dropwise at a rate of 1 mL / min. Control the magnetic stirring speed to 150 rpm. After the addition is complete, continue stirring and reacting for 5 hours. Then filter and collect the precipitate. After drying at 60°C, grind for 5 minutes to obtain silica powder.
[0069] (II) Weigh 1.5 g of γ-aminopropyltriethoxysilane and 0.7 g of glutaric anhydride, evenly disperse them in 50 mL of tetrahydrofuran and control the magnetic stirring rate to 200 rpm. React for 1 h, then add 10 g of silica powder and 10 mL of deionized water, continue to react for 4 h, then filter the precipitate, wash it with alcohol 3 times, and you can get carboxyl-modified silica particles.
[0070] (III) 1.5 g of the amino acid source was mixed with 10 mL of tert-butyl acetate, and the mixture was stirred in an ice bath for 20 min. Then, 0.5 mL of 45% perchloric acid was added to the system, and the magnetic stirring speed was adjusted to 150 rpm. The reaction was carried out for 5 h. Then, a sodium hydroxide solution with a molar concentration of 0.05 mol / L was used to adjust the pH of the system to 7. Ether was used for extraction, and the upper organic phase was taken and rotary evaporated at 35 °C to obtain a solid powder.
[0071] (IV) The solid powder was dispersed with 50 mL of acetone, and then carboxyl-modified silica particles were added, and the magnetic stirring speed was controlled to 300 rpm for 5 min, and then 0.4 g of aluminum chloride and 2 g of anhydrous sodium sulfate were added to the system, and the temperature was adjusted to 75 ° C, and the magnetic stirring speed was adjusted to 65 rpm, and the reaction was performed for 6 h. Then, the mixture was allowed to stand at room temperature for 12 h, and the solid part was filtered, washed with water twice, and filtered again, and the precipitate was added to 50 mL of dichloromethane solution, and 5 mL of trifluoroacetic acid was added under ice bath conditions. After stirring for 2.5 h, the precipitate was filtered again and dried to obtain a composite chelating agent.
[0072] Among them, the chemical composition (%wt) of low-grade molybdenite is: SiO269.27%, Al2O37.63%, MoS28.25%, CuFeS27.93%, CaO 3.24%, Fe2O31.25%, MgO 1.04%, and others 1.39%. The desorption solution is prepared by mixing petroleum ether and citric acid in a mass ratio of 525:1. The pre-solution is prepared by mixing anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate in a volume ratio of 50:20:12:1 and stirring at 45°C for 2h. The amino acid source is prepared by mixing citrulline, β-alanine, and γ-aminobutyric acid in a mass ratio of 6:15:5.
[0073] Example 3
[0074] The crystallization preparation method of ammonium heptamolybdate in the present embodiment is as follows:
[0075] (S01) Take 300g of low-grade molybdenite and crush it using a 125mmX150mm jaw crusher with a power of 3KW for 35 minutes. Then transfer the crushed material to a ball mill, control the ball mill speed to 135rpm, the ball-to-material ratio to 2:1, and grind for 2 hours to obtain molybdenum ore sand.
[0076] (S02) Put the molybdenum ore into a muffle furnace, control the temperature rise gradient to 8°C / min, rise to 650°C, then keep the temperature constant for 3 hours and then cool naturally to obtain molybdenum roasted sand.
[0077] (S03) Add molybdenum roasted sand into 5L of sodium hydroxide solution with a molar concentration of 2.5mol / L for dispersion, adjust the temperature to 45°C, stir at a speed of 150rpm, continue for 10h, and then filter to obtain a leachate.
[0078] (S04) Add 30 g of a composite chelating agent to the leachate, control the stirring speed to 150 rpm, and continue for 1 hour, then filter and collect the precipitate to obtain a chelate.
[0079] (S05) The chelate was added to 750 mL of desorption solution, stirred for 2 h, and then slowly heated to 65 °C at a rate of 5 °C / min, while ultrasonically controlling the ultrasonic frequency to 20.5 kHz for 1 h. The liquid phase was filtered and extracted with water to remove petroleum ether and impurities to obtain a sodium molybdate solution.
[0080] (S06) Take a sodium molybdate solution, add dilute sulfuric acid with a molar concentration of 0.05 mol / L, adjust the pH of the system to 5.5, then add ammonia water, adjust the pH to 7.0 again, and at the same time increase the system temperature to 70°C, adjust the stirring speed to 175 rpm, continue for 5 hours, then cool to 10.5°C with a cooling gradient of 0.5°C / min, let stand for 10 hours, take the bottom crystalline material, wash with alcohol and then crush to obtain ammonium heptamolybdate.
[0081] In this embodiment, the preparation steps of the composite chelating agent are as follows:
[0082] (I) Take 75 mL of the pre-solution and add 15 mL of ethyl orthosilicate dropwise at a rate of 1 mL / min. Control the magnetic stirring speed to 150 rpm. After the addition is complete, continue stirring and reacting for 5 hours. Then filter and collect the precipitate. After drying at 60°C, grind for 5 minutes to obtain silica powder.
[0083] (II) Weigh 1.5 g of γ-aminopropyltriethoxysilane and 0.7 g of glutaric anhydride, evenly disperse them in 50 mL of tetrahydrofuran and control the magnetic stirring rate to 200 rpm. React for 1 h, then add 10 g of silica powder and 15 mL of deionized water, continue to react for 5 h, then filter and collect the precipitate, wash it with alcohol 3 times, and you can get carboxyl-modified silica particles.
[0084] (III) 1.5 g of the amino acid source was mixed with 10 mL of tert-butyl acetate, and the mixture was stirred in an ice bath for 25 min. Then, 0.5 mL of 50% perchloric acid was added to the system, and the magnetic stirring speed was adjusted to 150 rpm. The reaction was carried out for 5 h. Then, the pH of the system was adjusted to 7 using a sodium hydroxide solution with a molar concentration of 0.05 mol / L. The mixture was extracted with ether, and the upper organic phase was taken and rotary evaporated at 40 °C to obtain a solid powder.
[0085] (IV) The solid powder was dispersed with 75 mL of acetone, and then carboxyl-modified silica particles were added, and the magnetic stirring speed was controlled to 300 rpm for 5 min, and then 0.5 g of aluminum chloride and 2 g of anhydrous sodium sulfate were added to the system, and the temperature was adjusted to 75 ° C, and the magnetic stirring speed was adjusted to 75 rpm, and the reaction was performed for 7 h. Then, the mixture was allowed to stand at room temperature for 12 h, and the solid part was filtered, washed with water 3 times, and filtered again, and the precipitate was added to 50 mL of dichloromethane solution, and 5 mL of trifluoroacetic acid was added under ice bath conditions. After stirring for 3 h, the precipitate was filtered again and dried to obtain a composite chelating agent.
[0086] Among them, the chemical composition (%wt) of low-grade molybdenite is: SiO269.27%, Al2O37.63%, MoS28.25%, CuFeS27.93%, CaO 3.24%, Fe2O31.25%, MgO 1.04%, and others 1.39%. The desorption solution is prepared by mixing petroleum ether and citric acid in a mass ratio of 550:1. The pre-solution is prepared by mixing anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate in a volume ratio of 110:40:24:3 and stirring at 45°C for 2h. The amino acid source is prepared by mixing citrulline, β-alanine, and γ-aminobutyric acid in a mass ratio of 8:15:5.
[0087] Comparative Example 1
[0088] The difference between this comparative example and Example 1 is that:
[0089] (III) 1.2 g of oleic acid was mixed with 5 mL of tert-butyl acetate, and the mixture was stirred in an ice bath for 5 min. Then, 0.3 mL of 35% perchloric acid was added to the system, and the magnetic stirring speed was adjusted to 100 rpm. The reaction was carried out for 3 h. Then, the pH of the system was adjusted to 6.5 using a sodium hydroxide solution with a molar concentration of 0.05 mol / L. The mixture was extracted with ether, and the upper organic phase was taken and rotary evaporated at 35 °C to obtain a solid powder.
[0090] The remaining steps are the same as those in Example 1.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 1 is that:
[0093] (S06) Take sodium molybdate solution, add ammonia water, adjust the pH to 7.0, and at the same time increase the system temperature to 70°C, adjust the stirring speed to 175 rpm, and continue for 5 hours, then cool to 25°C with a temperature reduction gradient of 0.5°C / min, let stand for 10 hours, take the bottom crystalline material, wash with alcohol, and then crush it, and collect it to obtain ammonium heptamolybdate crystals.
[0094] The remaining steps are the same as those in Example 1.
[0095] Comparative Example 3
[0096] The difference between this comparative example and Example 1 is that graphite oxide is used instead of carboxyl-modified silicon dioxide particles to prepare the composite chelating agent.
[0097] The average particle size of graphite oxide is 500 microns.
[0098] The remaining steps are the same as those in Example 1.
[0099] Performance testing
[0100] 1. With reference to GB / T657-2011 "Chemical Reagent Ammonium Molybdate Tetrahydrate (Ammonium Molybdate)", the performance test standards and test results of ammonium heptamolybdate prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 and Table 2, respectively.
[0101] Table 1 Performance test standards of ammonium heptamolybdate of Examples 1-3 and Comparative Examples 1-3
[0102]
[0103] Table 2 Performance test results of ammonium heptamolybdate of Examples 1-3 and Comparative Examples 1-3
[0104]
[0105] 2. The XRD pattern of the powder obtained by evaporating the sodium molybdate solution obtained in step (S05) of Example 1 and the XRD pattern of the ammonium heptamolybdate obtained in step (S06) are as follows: Figure 2 and Figure 3 shown.
[0106] By analyzing Examples 1-3 and Comparative Examples 1-3 and combining with Table 2, it can be seen that the purity of ammonium heptamolybdate prepared by the preparation methods of the examples is higher than that of the comparative examples, among which the ammonium heptamolybdate product obtained by the scheme of Example 1 has the highest purity and the impurity content is at a relatively low level.
[0107] Analyze Example 1 and Comparative Examples 1-3 and combine Table 2 and Figure 2-3 It can be seen that after replacing the carboxyl-modified silica particles in Example 1 with graphite oxide, the amino acid source with oleic acid, and changing the conditions for obtaining ammonium heptamolybdate by crystallization from sodium molybdate solution, the purity of the ammonium heptamolybdate product has declined significantly, and among the three comparative examples, the decline in comparative example 3 is the most obvious. This may be because comparative example 3 uses graphite oxide instead of carboxylated silica particles, and graphite oxide itself has a strong adsorption effect. During the adsorption treatment, in addition to the molybdate being adsorbed by the composite chelating agent, there are also more impurities adsorbed by graphite oxide. The impurities adsorbed by graphite oxide are mixed into the sodium molybdate solution during the desorption process, thereby causing the impurity content of ammonium heptamolybdate to be significantly increased. By adopting the preparation method of Example 1, regular and low-impurity ammonium heptamolybdate crystals can be obtained.
[0108] It can be seen from the analysis of Examples 1-3 and in combination with Tables 1-2 that the ammonium heptamolybdate prepared by the preparation method of the examples meets the national standards and industrial production requirements.
[0109] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a crystal of ammonium heptamolybdate, characterized in that: The steps include: (S01) taking low-grade molybdenite, crushing and ball-milling to obtain molybdenum ore sand; (S02) taking molybdenum ore and oxidizing and calcining it, adjusting the temperature gradient to 5-8°C / min, raising the temperature to 600-650°C, maintaining the temperature for 2-3h, and cooling to obtain molybdenum roasted sand; (S03) dispersing the molybdenum roasted sand with a sodium hydroxide solution, adjusting the temperature to 35-45° C., stirring and impregnating, filtering, and obtaining a leachate; (S04) adding a composite chelating agent to the leaching solution, stirring and immersing, and then filtering and collecting the precipitate to obtain a chelate; the composite chelating agent is prepared by reacting carboxyl-modified silica particles with an amino acid source; (S05) adding the chelate to a desorption solution for desorption treatment to obtain a sodium molybdate solution; (S06) taking a sodium molybdate solution, adding dilute sulfuric acid to adjust the pH for the first time, then adding ammonia water for ammonia leaching, adjusting the pH to 6.5-7.0 again, adjusting the temperature to 55-70°C, keeping the temperature constant for 3-5 hours, then cooling to 8.5-10.5°C at a temperature gradient of 0.5°C / min, standing for 8-10 hours, taking the bottom crystalline material, washing with alcohol and then crushing to obtain ammonium heptamolybdate; The amino acid source is prepared by mixing citrulline, β-alanine and γ-aminobutyric acid in a mass ratio of (0.5-0.8): (1.2-1.5): (0.3-0.5); The desorption liquid is prepared by mixing petroleum ether and citric acid in a mass ratio of (500-550):
1.
2. The method for preparing a crystal of ammonium heptamolybdate according to claim 1, wherein: In the step (S04), the preparation steps of the composite chelating agent are as follows: (I) adding ethyl orthosilicate dropwise to the pre-solution to react, filtering the precipitate, drying at 55-60°C, and grinding to obtain silicon dioxide powder; (II) mixing and dispersing the silane coupling agent and the acid anhydride, reacting, adding silica powder and water, continuing the reaction, and then filtering and washing the precipitate with alcohol to obtain carboxyl-modified silica particles; (III) Mixing an amino acid source with tert-butyl acetate, placing in an ice bath, adding an acid solution dropwise, reacting, and then adjusting the pH of the system to 6.5-7, extracting the organic phase, and rotary evaporating at 35-40° C. to obtain a solid powder; (IV) Dispersing the solid powder, adding carboxyl-modified silica particles, aluminum chloride and anhydrous sodium sulfate, and mixing, adjusting the temperature to 65-75°C, allowing the mixture to stand after the reaction, filtering the solid portion, washing with water and filtering again, dissolving the precipitate with dichloromethane, placing it in an ice bath, adding trifluoroacetic acid as an acidolysis agent, stirring, filtering the precipitate, and drying it to obtain a composite chelating agent.
3. A method for preparing ammonium heptamolybdate by crystallization according to claim 2, characterized in that: In the step (I), the pre-solution is prepared by mixing anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate in a volume ratio of (45-55): (15-20): (10-12): (1-1.5), and stirring at 30-45° C. for 1-2 hours.
4. The method for preparing a crystal of ammonium heptamolybdate according to claim 2, wherein: In the step (II), the silane coupling agent is γ-aminopropyltriethoxysilane; and the acid anhydride is any one of succinic anhydride and glutaric anhydride.
5. The method for preparing a crystal of ammonium heptamolybdate according to claim 2, wherein: In the step (III), the acid solution is perchloric acid with a mass concentration of 35%-50%.
6. The method for preparing a crystal of ammonium heptamolybdate according to claim 1, characterized in that: In the step (S05), the desorption process is: The chelate was mixed with the desorption liquid, stirred for 1-2 hours, then slowly heated to 55-65°C at a rate of 5°C / min, the ultrasonic frequency was controlled at 20-20.5kHz, ultrasonic treatment was performed for 0.5-1h, and filtered to obtain a solid phase and a sodium molybdate solution.
7. The method for preparing a crystal of ammonium heptamolybdate according to claim 1, characterized in that: In the step (S06), dilute sulfuric acid is added to adjust the pH to 4.2-5.5 for the first time.
Citation Information
Patent Citations
Preparation method of high-purity ammonium heptamolybdate
CN104649322A
Preparation method of novel silica gel-based hyperbranched PAMAM (polyamidoamine) chelating resin
CN102161758A
Environmentally-friendly efficient production process for ammonium molybdate
CN109650447A
Recovery of molyblenum
JP1986261215A